تطور عمارة المساجد والسمات المميزة لعناصرها الإنشائية - Tribak, Mohamed; Klaina, Mekki (Darul Yasin Al Sys, 2025)
الملخّص يتناول هذا البحث تطوّر عمارة المساجد في الحضارة الإسلامية من خلال تحليل عناصرها وخصائصها، وأدوارها الوظيفية، ومعانيها الرمزية. ويُبرز أهمية المسجد ليس فقط كمكان للعبادة، بل أيضًا كمؤسسة اجتماعية وحضرية مركزية في المجتمع الإسلامي. وعلى الرغم من قرون من التحوّلات المعمارية، فقد حافظ المسجد على هويته الفريدة وجوهره الروحي. وبالاستناد إلى أمثلة مختارة من الشرق الإسلامي والمغرب والأندلس، يتناول البحث السمات المعمارية المميّزة مثل القباب، والمآذن، والمحاريب، والمنابر، والتفاصيل الزخرفية. وتتمحور الإشكالية الأساس حول كيفية بقاء العمارة الإسلامية متجذّرة في المبادئ الدينية، مع تفاعلها في الوقت نفسه مع طيف واسع من التأثيرات الثقافية والفنية. ومن خلال منهج وصفي ومقارن، يؤكد البحث أن عمارة المساجد تمثّل تقليدًا ديناميكيًّا، راسخًا في القيم الإسلامية، وقادرًا على التكيّف مع التحوّلات التاريخية والسياقات الإقليمية، بما يعكس انفتاح الحضارة الإسلامية على الثقافات الأخرى دون التفريط في هويتها المعمارية المميّزة. Abstract This study explores the evolution of mosque architecture in Islamic civilization by analyzing its structural elements, functional roles, and symbolic meanings. It emphasizes the mosque’s significance not only as a place of worship but also as a central social and urban institution within Islamic society. Despite centuries of architectural change, the mosque has preserved its unique identity and spiritual essence. Drawing on selected examples from the Islamic East, the Maghrib, and al-Andalus, the study examines defining features such as domes, minarets, Mihrabs, Minbars, and ornamental details. The core question addresses how Islamic architecture has remained rooted in religious principles while interacting with a range of cultural and artistic influences. Employing a descriptive and comparative approach, the research contends that mosque architecture represents a dynamic tradition—firmly anchored in Islamic values yet adaptive to historical shifts and regional contexts, reflecting the civilization’s openness to other cultures without compromising its distinctive identity.